Invisible Wounds of War Summary and Recommendations for Addressing Psychological and Cognitive Injuries - Tanielian, Terri (RAND Corporation, 2008)
Summarizes key findings and recommendations from Invisible Wounds of War: Psychological and Cognitive Injuries, Their Consequences, and Services to Assist Recovery (Tanielian and Jaycox [Eds.], MG-720-CCF, 2008), a comprehensive study of the post-deployment health-related needs associated with post-traumatic stress disorder, major depression, and traumatic brain injury among veterans of Operations Enduring Freedom/Iraqi Freedom.